Paired terraces of the Seuti Khola, Dharan, eastern Nepal - Koirala, Matrika Prasad; Dwivedi, Sunil Kumar; Dhakal, Prakash; Neupane, Ghanashyam; Dhakal, Yadav Prasad; Khanal, Suresh Prasad; Regmi, Niraj Kumar; Ojha, Gobinda; Shrestha, Suchita; Dahal, Ranjan Kumar (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1276 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.80